Montmorillonite–Rifampicin Nanohybrid for pH-Responsive Release of the Tuberculostatic - Elmar Damasceno Junior; Raquel de Melo Barbosa; Rita de Cássia Dantas da Silva; Felipe dos Santos Costa; Djalma Ribeiro da Silva; César Viseras; Luana Perioli; Nedja Suely Fernandes (Pharmaceutics, 2023)
The present work describes the development of a hybrid and pH-responsive system for rifampicin using the clay mineral ‘montmorillonite’ as a nanocarrier. The influence of operational variables on the drug incorporation process was evaluated using 24 factorial designs. Under optimized conditions, the experiment allowed an incorporated drug dose equivalent to 98.60 ± 1.21 mg/g. Hybrid systems were characterized by different characterization techniques (FTIR, XRD, TGA, DSC, and SEM) to elucidate the mechanism of interaction between the compounds used. Through in vitro release studies, it was possible to verify the efficacy of the pH-dependent system obtained, with approximately 70% of the drug released after sixteen hours in simulated intestinal fluid. The adjustment of the experimental release data to the theoretical model of Higuchi and Korsmeyer–Peppas indicated that the release of rifampicin occurs in a prolonged form from montmorillonite. Elucidation of the interactions between the drug and this raw clay reinforces its viability as a novel carrier to develop an anti-TB/clay hybrid system with good physical and chemical stability.